Tinjauan Hukum Islam Terhadap Pengalaman Hidup Anak Yatim Piatu di Lingkungan Keluarga Asuh - N, Nurfianalisa; Sumardianti, Dwi; Maloko, Thahir (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Religious and spiritual knowledge are among the areas of education that must be given full attention by families for their children. Religious knowledge is very meaningful in awakening the instinctive spiritual strength and willingness that exists in children through religious guidance and the practice of religious teachings which are of course adapted to their level and age, so that it can help to gain basic religious knowledge which has implications for the child's awareness of running. religious teachings properly and correctly. The Koran explains about orphans in various ways, including religion, faith, property, inheritance, spoils of war, marriage, and so on. This shows that the problem of orphans in the Koran is not only a sosial and humanitarian problem, but is also related to religious and faith issues which will have an impact in the afterlife. Therefore, the problem of orphans in Islam is a very important matter, so it requires serious attention and handling from people who are caring and adequate. Allah commands those who believe and are pious to pay attention to, look after, assist, aid and protect orphans in the ways He has determined.